2000
DOI: 10.1002/1096-8628(20000612)96:3<422::aid-ajmg35>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

No relationship betweenTaq1 a polymorphism of dopamine D2 receptor gene and extrapyramidal adverse effects of selective dopamine D2 antagonists, bromperidol, and nemonapride in schizophrenia: A preliminary study

Abstract: The relationship between Taq1 A polymorphism of dopamine D(2) receptor (DRD(2)) gene and extrapyramidal adverse effects of bromperidol and nemonapride, which are both antipsychotic drugs with selective and potent DRD(2) antagonistic property, was investigated in Japanese schizophrenic inpatients. Twenty-seven patients were treated with bromperidol at 6 or 12 or 18 mg/day, while 25 patients were treated with nemonapride at 18 mg/day. The duration of treatment was 3 weeks. The A1 and A2 alleles were determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 16 publications
3
10
0
1
Order By: Relevance
“…Furthermore, no significant association between these polymorphisms and the intensity of the different types of EPS was noted, suggesting genetic variations in the DRD2 gene were not major predictors of the EPS resulting from antipsychotic treatment. This finding is similar to that of another study that demonstrated no significant differences in the incidence or severity of EPS, comparing subjects with and without the A1 allele of the DRD2 polymorphism [Mihara et al, 2000b]. Regarding the enzymes involved in the antipsychotic metabolism, three recent studies have found polymorphisms of various CYP2D6 are associated with EPS susceptibility [Jaanson et al, 2002;Schillevoort et al , 2002;Inada et al, 2003].…”
Section: Antipsychotic-induced Extrapyramidal Syndromessupporting
confidence: 90%
“…Furthermore, no significant association between these polymorphisms and the intensity of the different types of EPS was noted, suggesting genetic variations in the DRD2 gene were not major predictors of the EPS resulting from antipsychotic treatment. This finding is similar to that of another study that demonstrated no significant differences in the incidence or severity of EPS, comparing subjects with and without the A1 allele of the DRD2 polymorphism [Mihara et al, 2000b]. Regarding the enzymes involved in the antipsychotic metabolism, three recent studies have found polymorphisms of various CYP2D6 are associated with EPS susceptibility [Jaanson et al, 2002;Schillevoort et al , 2002;Inada et al, 2003].…”
Section: Antipsychotic-induced Extrapyramidal Syndromessupporting
confidence: 90%
“…On the other hand, previous studies have demonstrated that subjects with one or two A1 alleles of the DRD2 polymorphism at the Taq1 A locus present lower DRD2 density than those with no A1 allele [76]. Also, other studies have shown that female patients with the A1 allele exhibit greater prolactin response to nemonapride, a selective antagonist for D2-like dopamine receptors in schizophrenic patients [77]. Due to this association between TaqI and schizophrenia, the A1 allele has been suggested to diminish dopaminergic activity in the central nervous system [78].…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, these patients showed a better therapeutic response. 20 However, in agreement with Mihara et al 38 we could not find a significant association between adverse events measured by the EPS-score and the TaqIA 1 allele.…”
Section: Discussionmentioning
confidence: 99%